(untitled) (Tokyo, 2017)
In East Asia, the growth center of the post-Cold War world, two regional powerhouses survey one another from opposite sides of the Japan Sea. China, a rising power with tremendous economic clout and an increasingly assertive foreign and military policy, and Japan, a respected leader in the region and a mature nation enjoying its greatest political stability in many years, must coexist for the peace and prosperity of East Asia and the Asia-Pacific.
Keywords: Quan hệ quốc tế,International relations